KONTROVERSI PARA MUFASIR DI SEPUTAR TAFSÎR BI AL-ILMI - Sulthan Syahril (Millah: Journal of Religious Studies, 2009)
The following article examines the view of the mufasir (especially Imam Jamaluddin al-Suyuti, Sheikh Tantawi Jauhari, al-Zahabi and Mahmud Syaltut) tegarding the existence of the tafsîr bi al-ilmi and their arguments, how do four mufasir attitudes and respond towards the verses kauniyah in al-Qur’an? whether these verses are understood in the scientific level, or understood as Hidayah? Given that al-Qur’an is the “Book of Hidayah”. The method that used in this research is descriptive-analytical methods and comparative. The implementation of those three methods have been conducted together. The results of the research revealed that the controversy surrounding the mufasir concerning tafsîr bi al-ilmi appears due to the desire of each mufasir to show the correlation between science and the Qur’an as the holy book of all time and apply modern science that can correct used as a means to understand the greatness of God shown through His verses.